MORPHOLOGICAL FEATURES OF TESTES OF CHILDREN WHO DIED BEFORE THE AGE OF 6 MONTHS FROM HIV-INFECTED MOTHERS - Sherstiuk, S.A. (World of Medicine and Biology, 2012)
In of children who died before the age of 6 months from HIV-infected mothers showed reduced activity of the morphofunctional spermatogonia, Sertoli cells, Leydig cells, against growth of the stromal component. Identified morphological changes in testes of children died before the age of 6 months from HIV-infected mothers, apparently due to the influence of intrauterine and postnatal hypoxia on the background of maternal HIV infection, which provoked a compensatory stress of the body. Such changes may further cause of primary infertility.
Keywords: testes; HIV infection; children